Identifikasi Karakteristik Budaya Banyuwangi sebagai Alternatif Ikon Kota di Taman Sritanjung - Kurniawati, Mia; Kohdrata, Naniek; Semarajaya, Cokorda Gede Alit (Jurnal Arsitektur Lansekap; Vol. 10, No. 2 Oktober 2024DO - 10.24843/JAL.2024.v10.i02.p02, 2024)
Sritanjung Park is one of the city parks designed with the concept of a park as a green open space. The location of Sritanjung Park is in a very strategic location, namely in the middle of the city of Banyuwangi. This study aims to identify the typical culture of Banyuwangi that has the potential and can be used as a source of inspiration to characterize Sritanjung Park which describes the city of Banyuwangi. This research was conducted using an exploratory survey method. Data collection techniques through observation saw the condition of Sritanjung Park, interviews with community leaders, and literature studies from various sources of books, journals, and research reports related to Banyuwangi culture. The data collected were analyzed descriptively qualitatively. The results of the study explain that currently Sritanjung Park already has a character, namely gesah which means talking to each other, because the people of Banyuwangi are egalitarian (open). The story of the name Sritanjung should be the basis for planning Sritanjung Park, which is comfortable, safe and gives pride. Alternative recommendations for icons that emerged from this study were decorative lamps, batik motif chairs and barong kemiren motif chairs.